Pengaruh Rasio Profitabilitas, Rasio Solvabilitas, Dan Rasio Likuiditas Terhadap Return Saham Perusahaan Properti Dan Real Estate Yang Terdaftar Dalam Indeks Saham Syariah Indonesia (ISSI) Periode 2011 – 2014 - Novia Eka Fitri; Leo Herlambang (Universitas Airlangga, 2016)
This study aims to determine the effect of Return of Asset (ROA), Debt to Equity Ratio (DER), and Current Ration (CR) on stock return partially and simultaneously. The objects of the study are Property and Real Estate Company which registered in Indonesia Sharia Stock Index (ISSI) for four years, 2011-2014. This study used quantitative research. The writer used literature study and gathered secondary data for technique of data collection. This study finds that partially Return of Asset (ROA) significantly affects on stock return, while Debt to Equity Ratio (DER) and Current Ratio (CR) are not significantly affect on stock return. Simultaneously Return on Assets (ROA), Debt to Equity Ratio (DER) and Current Ration (CR) do not significantly affect on stock return.